Beyond PD-1: The Next Frontier for Immunotherapy in Melanoma - Rohatgi, Anjali; Kirkwood, John M. (Frontiers in Oncology, 2021)
The advent of first and second-generation immune checkpoint blockade (ICI) has resulted in improved survival of patients with metastatic melanoma over the past decade. However, the majority of patients ultimately progress despite these treatments, which has served as an impetus to consider a range of subsequent therapies. Many of the next generation of immunotherapeutic agents focus on modifying the immune system to overcome resistance to checkpoint blockade. ICI resistance can be understood as primary, or acquired—where the latter is the most common scenario. While there are several postulated mechanisms by which resistance, particularly acquired resistance, occurs, the predominant escape mechanisms include T cell exhaustion, upregulation of alternative inhibitory checkpoint receptors, and alteration of the tumor microenvironment (TME) into a more suppressive, anti-inflammatory state. Therapeutic agents in development are designed to work by combating one or more of these resistance mechanisms. These strategies face the added challenge of minimizing immune-related toxicities, while improving antitumor efficacy. This review focuses upon the following categories of novel therapeutics: 1) alternative inhibitory receptor pathways 2) damage- or pathogen-associated molecular patterns (DAMPs/PAMPs) and 3) immune cell signaling mediators We present the current state of these therapies, including preclinical and clinical data available for these targets under development.